Pengaruh Keahlian Akuntansi, Self-Regulated Learning, Literasi Digital dan Efikasi Diri Terhadap Kesiapan Kerja Calon Akuntan di Era Disrupsi Digital pada Mahasiswa Prodi Akuntansi UIN Sunan Ampel Surabaya - Rizky Rizaldi Al-Mubarak; Binti Shofiatul Jannah (Yayasan Almanar Pujud, 2024)
This study aims to examine the influence of accounting expertise, self-regulated learning, digital literacy and self-efficacy on the work readiness of prospective accountants in the era of digital disruption in accounting students of FEBI UIN Sunan Ampel Surabaya. This study uses a quantitative approach. The population of this study were active accounting students of FEBI UIN Sunan Ampel Surabaya. The sample used in this study was 116 respondents using convenience sampling techniques. The data used in this study are primary data obtained through questionnaires. The data analysis technique uses multiple linear regression analysis. Based on the results of this study, it is proven that accounting expertise has a positive and significant effect on the work readiness of prospective accountants, self-regulated learning has a positive and significant effect on the work readiness of prospective accountants, digital literacy has a positive and significant effect on the work readiness of prospective accountants, self-efficacy has a positive and significant effect on the work readiness of prospective accountants.